Physician Practices and the Late Adoption of Transparent Peer Comparisons for Performance Feedback. (20th August 2020) - Hague, E.; Comfort, L.; Rosenthal, M.; Shortell, S.; Rodriguez, H.
Abstract : Research Objective: Over the past two decades, health care organizations have recognized the importance of physician feedback and data transparency for continuous performance improvement. Diffusion of innovation theory suggests that late‐adopting organizations face unique barriers to adoption, particularly of innovations that require infrastructure investments. This study aims to identify qualities associated with physician practices' late or non‐adoption of unblinded peer comparisons for performance reporting. Study Design: This research draws on the cross‐sectional 2017/2018 National Survey of Healthcare Organizations and Systems (NSHOS) practice‐level survey (response rate=47%) linked to 2017 IQVIA OneKey data on physician practices. Predictors of unblinded performance feedback include composites of organizational learning orientation, organizational capacity for innovation, health information technology (HIT capabilities), and participation in delivery reform initiatives. We perform a logistic regression to estimate the odds that a practice does not report using unblinded peer comparison feedback, controlling for reported practice ownership, a measure of physician influence on practice priorities and strategies, Medicaid revenue (less than 30% or ≥30%, as a proxy for financial resources and patient complexity), and practice size (physician count). Population Studied: We study the population of practices with at least three primary care physicians using a nationally representative sample of 2, 190 non‐federal physician practices. Practices are of diverse ownership, including primary care and multispecialty provider groups, those owned by healthcare systems, independent practices, and other arrangements. Principal Findings: 27% of physician practices did not report using unblinded peer comparisons for performance feedback reports. These physician practices had lower organizational learning orientation (OR=0.689, p<0.001), lower HIT capabilities (OR = 0.725, P  < .001), and less participation in delivery reform initiatives (OR = 0.740, P  < .001). No significant association was found between organizational capacity for innovation and late adopter status. Of control variables, health care system ownership or ownership by some other entity, and "some" physician influence (compared to "little to none" or "a lot") were found to be significantly associated with practice use of transparent performance comparisons. Our Medicaid revenue variable was not found to be significant. Conclusions: Physician practices that do not use unblinded peer comparisons for performance feedback have lower organizational learning orientations, lower HIT capabilities, and participate in fewer delivery reform initiatives than adopters of transparent reporting. These findings indicate that late or non‐adopting practices may be less motivated toward learning, and external quality incentives may be less important influences on their innovation adoption. HIT capabilities and economies of scale related to practice ownership may also improve adoption of transparent performance reporting. Implications for Policy or Practice: Physician practices which have not adopted transparent performance reporting have lower orientation to organizational learning, lag in their expansion of HIT capabilities, and participate in fewer reform initiatives. This suggests that policies and programs which encourage performance transparency, such as Medicare's Quality Payment Program, should be attentive to the resource needs and infrastructure considerations of late or non‐adopters. Primary Funding Source: Agency for Healthcare Research and Quality.